Simulation Based Lectures for Students in Logistics - Bjorbæk, C. T.; Berg, Ø.; Schuett, H.; Dushenko, M. (Scientific Journal of Gdynia Maritime University, 2018)
Automation and digitalization in logistic processes nowadays increase the complexity of logistic systems (supply networks, terminals and warehouses) and leads to highly linked systems. Their dimensioning as well as start-up and optimization of operational processes require technical assistance today. Simulation is used for understanding the behaviour of the seaport terminal and analysing the interaction of the complex processes at the terminal. This paper will show an investigation of the usage of specific port terminal simulator in the education of logisticians at university. It will show the effects of using simulation within the lessons in respect to the understanding of port operation and port simulation.